The utilization of the geographic information system in the environmental problems evaluation of Itajubá city - Grilo, Roseana Corrêa [UNESP]; Foresti, Celina [UNESP]; De Freitas Viadana, Maria Isabel C. [UNESP] (My University, 2000)
The environmental problems are constancet in many cities of the world and maked it difficult for human life. In Itajuba city (located in 22 26′ S of latitude and 45 27′ W, in South of Minas Gerais State in Brazil) there are several problems, because the occupation of this area is inadequate. The city expansion in a plain where the principal river is Sapucai, that divides the urban space in two parts (from east to west). The development also occurred in slope.during the last time. In this research utility many technics with the cartographic, the photo interpretation of thirty air pictures(aerial photos) and use of the GIS. In the digitization of the planimetric plans (blocks plan, pluvial system plan, hidrography and contour line map) scale 1:10000 from 1981 and 1998 of Itajuba city was used the software AutoCad R-14. In following a map was elaborated about the use of the urban soil resulting the photo interpretation. The software IDRISI FOR WINDOWS 2.0 was used to elaborate the declivity of map and to cross this data with the map use of the urban soil (1981). After crossing the data with the blocks plan (1999). Many consideration were made for example:1) the city expansion in Sapucai plain, right riverside affluent Ribeirão Jose Pereira, Ribeirão Agua Preta and left affluents Ribeirão Anhumas and Ribeirão Piraguçu further on the slops 2) this urban development, without planning with occupation of the river plain and the intersection-cross-tabulation of data in IDRISI FOR WINDOWS 2.0, demonstrated that there are many environmental problems. In Itajuba city: during the flood rivers, in summer, which is the rain station, due to the inadequate occupation of 1, 782 Km2 the inundation of plain, the population suffer (thereare many unifamiliar residential in this area); 3) other problem is the pluvial system that is insufficient during the pluvial period, that contribute for overflowing and crumbling in the occupation of the slops whithout vegetation and paviment. The research demonstrated that in Itajuba city there are several problems that result of the expansion and occupation of the uncontrolled use of the urban soil in Itajuba city.
Keywords: Environmental problems; Geographic information system; Remote sensing; Urban space